Structure‐Based Programming of Supramolecular Assemblies in Living Cells for Selective Cancer Cell Inhibition. (26th July 2021) - Hu, Liangbo; Li, Ying; Lin, Xinhui; Huo, Yucheng; Zhang, Hongyue; Wang, Huaimin
Abstract: Here we report on the design, synthesis, and assembly of an enzymatic programmable peptide system inspired by endocytic processes to induce molecular assemblies formation spatiotemporally in living cancer cells, resulting in glioblastoma cell death mainly in necroptosis. Our results indicate the stability and glycosylation of molecules play an essential role in determining the final bioactivity. Detailed mechanistic studies by CLSM, Flow cytometry, western blot, and Bio‐EM suggest the site‐specific formation of assemblies, which could induce the LMP and activate the downstream cell death pathway. Moreover, we also demonstrate that our strategy can boost the activity of commercial chemotherapy drug by escaping lysosome sequestration. We expected this work would be expanded towards artificial intelligent biomaterials for cancer therapy and imaging precisely. Abstract : By integration of the endocytotic process and the overexpressing enzyme within lysosome in cancer cells, we construct enzymatic programmable assemblies selectively in living cancer cells for glioblastoma cancer therapy.